The Letters of Robert Frost, Volume 3 1929-1936 - Frost, Robert 1874-1963 (Harvard University Press, 2021)
The third installment of Harvard's five-volume edition of Robert Frost's correspondence. The Letters of Robert Frost, Volume 3: 1929-1936 is the latest installment in Harvard's five-volume edition of the poet's correspondence. It presents 589 letters, of which 424 are previously uncollected. The critically acclaimed first volume, a Times Literary Supplement Book of the Year, included nearly 300 previously uncollected letters, and the second volume 350 more. During the period covered here, Robert Frost was close to the height of his powers. If Volume 2 covered the making of Frost as America's poet, in Volume 3 he is definitively made. These were also, however, years of personal tribulation. The once-tight Frost family broke up as marriage, illness, and work scattered the children across the country. In the case of Frost's son Carol, both distance and proximity put strains on an already fractious relationship.